Transient central precocious puberty: a new entity among the spectrum of precocious puberty? - Valentina Assirelli; Federico Baronio; Rita Ortolano; Giulio Maltoni; Stefano Zucchini; Valeria Di Natale; Alessandra Cassio (BMC, 2021)
Abstract Objective Recently, we observed some cases of Precocious Puberty (PP) with a partial central activation of hypothalamic-pituitary-gonadal (HPG) axis that tended to normalized in 6-12 months. To evaluate the frequency of this form within the spectrum of forms of PP, we retrospectively assessed the clinical, hormonal and ultrasound characteristics of patients attending to our Center for signs of PP, between 2007 and 2017. To hypothesize some causes of this "pubertal poussée" a questionnaire about environmental data was provided to patients. Methods 96 girls were recruited for the study and divided into three Groups. Group 1: 56 subjects with Central PP (CPP) requiring treatment with GnRH analogue; Group 2: 22 subjects with transient activation of pubertal axis, that tended to normalize, "Transient CPP"(T-CPP); Group 3: 18 subjects with Isolated Thelarche (IT). Results Mean age at diagnosis was 6.8 ± 1.0 years in Group 1, 5.9 ± 1.3 years in Group 2 and 5.6 ± 1.5 years in Group 3. A significant increase of diagnosis of T-CPP was observed over the study period. Significantly higher use of some homeopathic medicines and potential exposure to pesticides was reported in Group 2 vs Group 1. Conclusions To our knowledge, we first reported a form defined as T-CPP, characterized by partial activation in the HPG axis normalizing over time. An increased use of homeopathic medicines and exposure to environmental pollutants in these patients was evidenced.